2018
DOI: 10.1136/bmjopen-2018-021979
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on survival of medical patients with sepsis: a prospective cohort study in a university hospital in China

Abstract: ObjectiveTo evaluate the impact of body mass index (BMI) on survival of a Chinese cohort of medical patients with sepsis.DesignA single-centre prospective cohort study conducted from May 2015 to April 2017.SettingA tertiary care university hospital in China.ParticipantsA total of 178 patients with sepsis admitted to the medical intensive care unit (ICU) were included.Main outcome measuresThe primary outcome was 90-day mortality while the secondary outcomes were in-hospital mortality, length of ICU stay and len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…It is may be related to a worsened nutritional status of patients with COVID-19 from the ICU or geriatric ward. A similar phenomenon was also observed by other previous studies; for example, patients with BMI < 20 had greater 60-day mortality in the ICU setting (47); lower BMI was associated with a higher risk of death for patients with sepsis (48); patients who are underweight have a higher mortality rate in the pediatric ICU (49). Hence, patients with COVID-19 from the ICU or geriatric ward may need to maintain BMI within the normal range.…”
Section: Discussionsupporting
confidence: 83%
“…It is may be related to a worsened nutritional status of patients with COVID-19 from the ICU or geriatric ward. A similar phenomenon was also observed by other previous studies; for example, patients with BMI < 20 had greater 60-day mortality in the ICU setting (47); lower BMI was associated with a higher risk of death for patients with sepsis (48); patients who are underweight have a higher mortality rate in the pediatric ICU (49). Hence, patients with COVID-19 from the ICU or geriatric ward may need to maintain BMI within the normal range.…”
Section: Discussionsupporting
confidence: 83%
“…Over the years, whether BMI was associated with altered mortality of patients with severe sepsis has been rarely reported in Asian population; we only found one single-center study with a small sample size (sepsis n = 178) conducted in a Chinese population. In the Chinese study, patients with a BMI < 18.5 had the highest 90-day mortality (66.7%) compared to the other subgroups with BMI ≥ 18.5 (18.2–48.0%) 7 . In accordance with these findings, the present study that enrolled 2175 patients with severe sepsis in total verified the increased mortality in patients with a BMI < 18.5.…”
Section: Discussionmentioning
confidence: 86%
“…By contrast, patients with a low BMI significantly increased blood IL-6 levels compared to those with a high BMI in North America 3 . However, studies regarding BMI in sepsis in Asian populations are limited; after the publication of the systematic review, a single-center study of sepsis with a small sample size in China reported that patients with a low BMI had increased mortality 7 . Non-obese patients were more common in Asian countries than in Europe and North America 8 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review from 2017 found markedly reduced mortality from sepsis among overweight and obese patients compared with those of normal weight [18]. Other hospital-based studies have reported similar findings [12][13][14][15], including a recent study of approximately 55,000 patients from 139 hospitals in the United States [17].…”
Section: Discussionmentioning
confidence: 87%
“…Traditional observational studies of general populations have found body mass index (BMI) to be positively associated with risk of BSI or sepsis [7][8][9][10], and above-normal BMI to be associated with BSI or sepsis mortality [7,9,11]. However, studies restricted to patients with BSI or sepsis have observed a considerable reduced mortality risk with increasing BMI [12][13][14][15][16][17], including a systematic review from 2017 [18]. It has therefore been advocated that one should study in what way obesity is protective for sepsis mortality, and that this may help inform new therapeutic strategies [17,18].…”
Section: Introductionmentioning
confidence: 99%